Health information systems (HIS) adoption success factors in Nigeria - Aileakhue, Musa Hanifah (Kulliyyah of Information and Communication Technology ,International Islamic University Malaysia, 2022)
The Health information system is the application of information technology to enable and promote health care services provision, support and delivery. The implementation of this system is directed at assisting medical institutions to store patients’ health record in an electronic based method. In order to manage lots of information, the health information system comes in handy to sort data, processes and people. The system which consists of a set of interrelated components gathers, stores, and disseminates health or organizational related information of individuals working in the same health sector. All around the world the applications of digital health technology have become vital tools of modern information technology which has aided in the smooth and efficient delivery of quality healthcare. As much as there have been a lot of derived benefits mostly in the developed countries, studies have shown that the success of the electronic health information system implementation in developing countries is still low, and various reasons have however been identified as the cause of this poor outcome. Therefore this study aims to identify, investigate and analyze the factors that will determine the successful implementation of the health information system in health institutions in Nigeria, being a developing country with an approximate population of 200 million people; and how these factors can be enhanced using an IS success model, in order to achieve a successful implementation that will yield the desired results. Findings from this study show that attention should be on updating and upgrading the Information System quality dimensions (service Quality, Information Quality, and System Quality) as it reveals that there is a high dependence on these dimensions to bridge the research gap; as results show that there is an overall correlation between the analyzed variables. Health practitioners should be trained on how to utilize the system in order to improve their attitudes and perceptions towards it. Doing this will increase the zeal to utilize the system as the users will be motivated to make it habitual to use the system and better goals will be attained. Also the results and findings will be very relevant to health institutions especially in developing countries and other researchers as well, as they can apply the IS success model in similar research and in other settings.